ДИАЛОГ В КУЛЬТУРЕ: ВОЗМОЖНОСТИ И ОГРАНИЧЕНИЯ - ТКАЧЕВА, Е. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
В данной статье рассматриваются проблемы возможностей и ограничений диалога культур в современном обществе. Автор анализирует ситуации взаимодействия культур и осуществляет попытку рассмотреть возможности диалога культур в условиях глобализации, а также уточнить принципы организации диалога между современными цивилизациями под углом зрения их социокультурных систем. О.В. Ткачова ДІАЛОГ В КУЛЬТУРІ: МОЖЛИВОСТІ ТА ОБМЕЖЕННЯ У даній статті розглядаються проблеми можливостей та обмежень діалогу культур у сучасному суспільстві. Авторка аналізує ситуації взаємодії культур та здійснює спробу розглянути можливості діалогу культур в умовах глобалізації, а також уточнити принципи організації діалогу ___________________ © Ткачева Е.В. , 2011 Ключові слова: діалог, мультикультуралізм, толерантність, культурна ідентичність, глобалізація. E. Tkacheva DIALOGUE IN THE CULTURE: POSSIBILITIES AND LIMITS This article discusses the problem of the opportunities and constraints of cultural dialogue in modern society. The author analyzes the situation of interaction between cultures and attempts to consider the possibilities of intercultural dialogue in the context of globalization, as well as to clarify the principles of dialogue between contemporary civilizations from the perspective of their sociocultural systems. Keywords: dialogue, multiсulturalism, tolerance, cultural identity, globalization